Apelin and chemerin receptors are G protein-coupled receptors involved in metabolic as well as reproductive functions: Potential therapeutic implications?. (February 2021) - Estienne, Anthony; Bongrani, Alice; Froment, Pascal; Dupont, Joëlle
Abstract: Adipokines are a large group of polypeptide hormones secreted by white adipose tissue able to interact through different receptors with several organs, including liver, central nervous system and gonads. In this review, we will focus on the adipokines that mediate their effects through G protein-coupled receptors, namely apelin and chemerin. Firstly, we will review their structure and that of their receptors (APJ for apelin, CMKLR1, GPR1 and CCRL2 for chemerin), as well as their tissue distribution and molecular mechanisms. In the second part of the review, we will focus more in detail on the known metabolic and reproductive effects of these receptors, in both physiological and pathological conditions, underlining their relevant potential clinical implications.